Book Review: A Study of Mixed Legal Systems: Endangered, Entrenched or Blended - Esteban Ciangarotti González (Oñati Socio-Legal Series)
Book review of Sue Farran, Esin Örücü and Sean Patrick Donlan. A Study of Mixed Legal Systems: Endangered, Entrenched or Blended. Farnham; Burlington, Ashgate, 2014. pp. 256. ISBN 978-1-4724-4177-5 (hbk). £75,00.